Secretory system in Cuphea calophylla (Lythraceae): the bi-compartmentalization of epidermal cells, reclassification of glandular appendages, and the first report of hydathodes - Seixas, Diana Pacheco [UNESP]; Rodrigues, Tatiane Maria [UNESP] (Canadian Science Publishing, 2022)
Cuphea calophylla Cham. & Schltdl. is a Lythraceae subshrub that occurs in different environmental conditions. The aerial portions of this plant have medicinal properties and are used for soap production. We assessed the structure, ultrastructure, and histochemistry of the secretory cells and tissues in C. calophylla leaves and stems to further understand its secretory sys-tem. Hydathodes with epithem, tracheary elements, and water pores occur at the leaf border and are here described for the first time for a Cuphea species. Glandular appendages occur in leaves and stems and are characterized by a wide basis and a narrower apical portion that exuded sticky material. Ontogenetical analysis showed that these appendages are glandular emergences; phenolic compounds, mucilage, and lipids were produced in their cells which exhibited Golgi bodies, vesicles, smooth endoplasmic reticulum, oil drops, and plastids. The epidermis of the leaf blade has bi-compartmentalized secretory cells divided by a cellulosic septum in their equatorial region. These cells contain phenolic compounds in the upper compartment and mucilage in the lower compartment. Our results shed light on the sites producing bioactive compounds in C. calophylla and expand the knowledge on the secretory system in Lythraceae, promoting a reclassification and an identification of new structures.
Keywords: Cuphea calophylla Cham. & Schltdl; histology; hydathodes; secretory emergences; secretory epidermal cells; ultra-structure